PROMOTION FOR ORGANIC FARMING IS ESSENTIAL (International Journal of Food and Nutritional Sciences, 2021)
Today's era is one of globalization privatization and liberalization. That is, since 1991, strong winds ofcapitalism are blowing in India directly and indirectly. Capitalismfavours imperial entrepreneurs and capitalists.Mass production is done for profit. High yielding hybrid seeds are used for production. The consumption of Gavranseeds is reduced